Skema Investasi Hibrida Pada Struktur Joint Venture dalam Penanaman Modal Asing Di Indonesia - Mochammad Rizky Arie Syadewa (LPPM Universitas Ekasakti Padang, 2023)
Foreign investment in Indonesia has an important role in driving the national economy, one of which is through direct foreign investment through joint ventures, however, there are still many foreign investment activities carried out under contractual schemes where the government and the state community the recipient of the investment is not actively involved. So, it is necessary to transform into a corporate joint venture scheme as an alternative to a hybrid investment scheme so that it can have a positive impact on the development of the Indonesian economy, namely ensuring the sustainability of business in Indonesia and actively involving the government and the community. This research was conducted with a conceptual approach. This research will be a reference for investment politics in Indonesia which is oriented towards the sustainability and active participation of investment recipient countries.